2012
DOI: 10.1117/12.923100
|View full text |Cite
|
Sign up to set email alerts
|

Photonic chip based tunable slow and fast light via stimulated Brillouin scattering

Abstract: The ability to control the speed of light on an optical chip is fundamental to the development of nanophotonic components for alloptical signal processing and sensing [1][2][3][4][5][6][7]. However this is a significant challenge, because chip-scale waveguides require very large changes in group index (Δn g ) to achieve appreciable pulse delays. Here, we use Stimulated Brillouin Scattering (SBS) to report the demonstration of on-chip slow, fast and negative group velocities with Δn g ranging from −44 to +130, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 17 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…The important parameter in a slow-light device Principle of Brillouin slow-light demonstrating pulse delay when the pump was turned on. A probe pulse centered at the Stokes (anti-Stokes) frequency ω s (ω as ) experiences large positive (negative) index slope resulting in slow-(fast-) light [57]. Copyright 2012, Optical Society of America.…”
Section: On-chip Slow-and Fast-lightmentioning
confidence: 99%
See 2 more Smart Citations
“…The important parameter in a slow-light device Principle of Brillouin slow-light demonstrating pulse delay when the pump was turned on. A probe pulse centered at the Stokes (anti-Stokes) frequency ω s (ω as ) experiences large positive (negative) index slope resulting in slow-(fast-) light [57]. Copyright 2012, Optical Society of America.…”
Section: On-chip Slow-and Fast-lightmentioning
confidence: 99%
“…This shows that the chip-based SBS slow-light device is not only compact but is highly efficient as well. While tunable delays can be obtained using SBS slow-and fast-light, recently it was shown that dynamic Brillouin gratings can be used to achieve large Group-index measurements for (a) slow-light and (b) fast-light regime using SBS in a photonic chip [57]. Copyright 2012, Optical Society of America.…”
Section: On-chip Slow-and Fast-lightmentioning
confidence: 99%
See 1 more Smart Citation
“…On-chip SBS has been demonstrated on a chalcogenide (As 2 S 3 ) on silica (SiO 2 ) platform with gains approaching 23 dB [5]. Using this integrated platform, microwave photonic bandpass filters have been demonstrated with a bandwidth of 20 MHz-40 MHz [6].…”
Section: Introductionmentioning
confidence: 97%
“…It is a nonlinear phenomenon arising from the interaction between propagating optical and acoustic waves [1,2]. The high sensibility of SBS to external conditions allows to realize several applications such as slow light generation [3,4], ber ampliers and lasers [5,6], and distributed ber sensors [7]. Among the Brillouin based applications, Brillouin sensors have gained considerable interest due to their various and several usefulness and their interesting applications in civil structures as well as in smart devices [10,11].…”
Section: Introductionmentioning
confidence: 99%